2013
DOI: 10.1055/s-0032-1329896
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Portosystemic Shunts in Children: Recognition, Evaluation, and Management

Abstract: Congenital portosystemic shunts are present in one in 30,000 children. Among the associated risks of severe complications are neonatal cholestasis, benign and malignant liver tumors, hepatopulmonary syndrome, portopulmonary hypertension, and encephalopathy. They can be detected on prenatal ultrasonograms, during the investigation of a positive galactosemia screening test in neonates or of a complication, or be found fortuitously on an abdominal ultrasound. Small intrahepatic shunts may resolve spontaneously wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
352
2
35

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(399 citation statements)
references
References 157 publications
10
352
2
35
Order By: Relevance
“…Various imaging modalities and blood tests indicated that the natural histories of intrahepatic and extrahepatic CPSSs differed. Intrahepatic CPSS without hepatic tumor has been reported to spontaneously close or regress, whereas extrahepatic CPSS does not spontaneously regress (3,7,8,(16)(17)(18). Ultrasonography and dynamic contrast-enhanced CT evaluation showed spontaneous reductions in the shunt size in all of our patients with intrahepatic CPSS but in none with extrahepatic CPSS, strengthening the previous findings.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Various imaging modalities and blood tests indicated that the natural histories of intrahepatic and extrahepatic CPSSs differed. Intrahepatic CPSS without hepatic tumor has been reported to spontaneously close or regress, whereas extrahepatic CPSS does not spontaneously regress (3,7,8,(16)(17)(18). Ultrasonography and dynamic contrast-enhanced CT evaluation showed spontaneous reductions in the shunt size in all of our patients with intrahepatic CPSS but in none with extrahepatic CPSS, strengthening the previous findings.…”
Section: Discussionsupporting
confidence: 86%
“…Surgical repair or embolization may be recommended for extrahepatic CPSS without closure because of the high risk of hepatopulmonary syndrome, pulmonary hypertension, and hepatic encephalopathy (4,7,8,(13)(14)(15)(16). Stringer (8) described that CPSS-affected individuals are at risk of developing hepatic encephalopathy and/or an intrahepatic tumor depending largely on the volume and duration of the shunt.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…- 8 , 11 It may also be associated with: membranoproliferative glomerulonephritis, hyperinsulinemia with hyper- and hypoglycemia, hypothyroxinemia, hyperandrogenism, pancreatitis, and heart failure 812 There are reports in the literature suggesting that IUGR, as seen in our patient, may also be shunt-related 89 , 13 The explanation for IUGR is the reduction of liver perfusion caused by the shunt.…”
Section: Discussionmentioning
confidence: 60%